Two Essays on Build-ups of Systemic Risk - Szabo, Milan (2017)
This thesis contains two essays that discuss measuring of systemic risk during the buildup phase. I lay theoretical foundations to the measuring of systemic risk, define systemic risk, discuss its buildups, and its endogenous nature. Following the theoretical framework, I propose two models. The first model, from the first essay, presents an early warning model built on systemic banking crises identified in 40 countries throughout a period 1970Q1:2010Q4. I put forth (i) a clear evidence of the endogenous character of systemic risk, as they are preceded by periods of credit booms, leveraging, and excessive growths in asset prices, (ii) I construct a regulator's loss function with respect to false negative and false positive errors, and (iii) outline a cost-benefit analysis of macroprudential policy while using the model framework. The second essay explores market based approach to measure systemic risk. Employing the methodology of regime switching models for week-to-week changes of TED spread starting with observations from 2011, I present another approach that can be applied to capture abrupt changes in systemic risk. Identified tumult periods are related to possible events that may stay behind the turmoils, when in particular, the new regulation amendments of money market funds are discussed.